2017
DOI: 10.1063/1.4978961
|View full text |Cite
|
Sign up to set email alerts
|

SQUID-based current sensing noise thermometry for quantum resistors at dilution refrigerator temperatures

Abstract: We present a dc Superconducting QUantum Interference Device (SQUID)-based current amplifier with an estimated input referred noise of only 2.3 fA/Hz. Because of such a low amplifier noise, the circuit is useful for Johnson noise thermometry of quantum resistors in the kΩ range down to mK temperatures. In particular, we demonstrate that our circuit does not contribute appreciable noise to the Johnson noise of a 3.25 kΩ resistor down to 16 mK. Our circuit is a useful alternative to the commonly used High Electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…We use the current-sensing circuit described in [26], which consists of a commercial dc-SQUID [30] connected to an impedance matching superconducting transformer of effective turn ratio 212. We found that when a R = 3.25 kΩ source resistor is connected to this current amplifier, the overall gain is R T = V out /I pr = 2.25 GΩ, the circuit bandwidth is 600 Hz, and the amplifier noise is 2.3 fA ( √ Hz) −1 .…”
Section: Low Pass Filtermentioning
confidence: 99%
See 3 more Smart Citations
“…We use the current-sensing circuit described in [26], which consists of a commercial dc-SQUID [30] connected to an impedance matching superconducting transformer of effective turn ratio 212. We found that when a R = 3.25 kΩ source resistor is connected to this current amplifier, the overall gain is R T = V out /I pr = 2.25 GΩ, the circuit bandwidth is 600 Hz, and the amplifier noise is 2.3 fA ( √ Hz) −1 .…”
Section: Low Pass Filtermentioning
confidence: 99%
“…Here V out is the output voltage of the SQUID electronics and I pr the primary current of the transformer. In this circuit, the impedance matching transformer was mounted on the mixing chamber of a dilution refrigerator, located in the cancellation region of a 10 T superconducting solenoid [26].…”
Section: Low Pass Filtermentioning
confidence: 99%
See 2 more Smart Citations
“…The much higher sensitivity of dc-SQUIDs allowed one to open up the bandwidth and thus speed up the measurement process by several orders of magnitude. Following up this work about 15 years later, practical current noise thermometers were developed and characterized over a wide range of temperatures [35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%